A Planar‐Chiral Palladium Complex Derived from a Weak Oxygen Donor N, N‐Diisopropyl Ferrocenecarboxamide Ligand. Issue 1 (2nd January 2023) - Thorat, Raviraj Ananda; Mandhar, Yogesh; Parganiha, Devendra; Patil, Khushbu Bindesh; Singh, Vikram; Shakir, Batul; Raju, Saravanan; Kumar, Sangit
Abstract: The reaction of chiral 2‐iodoferrocenecarboxamide, palladium(II) acetate, and triphenylphosphine ligand in acetonitrile has been resulted in the formation of an air‐stable chiral ( Sp )‐2‐( N, N ‐diisopropyl ferrocenecarboxamide) triphenylphosphine palladium(II) iodide complex. The isolated chiral palladium complex was thoroughly characterized by multi‐nuclear ( 1 H, 13 C, 31 P) NMR, IR spectroscopy, mass spectrometry, polarimetry, CHN analysis, cyclic voltammetry and single crystal X‐ray crystallography (XRD). The single‐crystal XRD analysis reveals a square planar geometry around the palladium atom with a strong amide oxygen‐Pd bond [2.095(6) Å]. The palladium complex crystallized in the C2 ‐chiral space group having a Flack parameter value of 0.011(14), which is close to 0 and indicative of the enantiomeric purity of the palladium complex. The electrochemical study reveals a two‐electron redox couple due to the ferrocenyl Fe(II) atom and the palladacyclic Pd(II) center. In differential pulse voltammetry (DPV), two peaks were observed at 450 mV and 590 mV vs. Ag/AgCl. Further, the synthesized chiral palladacyle has also been explored in Suzuki‐Miyaura coupling reaction as a substrate and as a catalyst for Tsuji‐Trost coupling and phosphonation reactions. Abstract : A stable chiral palladium ferrocene complex was prepared from N, N ‐diisopropylferrocene carboxamide ligand. Chiral Pd‐complex was explored for Suzuki‐Miyaura coupling reaction for the preparation of enantiomerically pure 2‐arylferrocenecarboxamides. Further catalytic application were studied in cross coupling of aryl bromides with phosphite and Tsuji‐Trost reaction.